Photochemical Studies of Bipyridyl/γ-Picoline Adduct of bis-(4,5-Dimethyl-1,3,2-dioxaphospholane-2-thione-2-thiolato) nickel (II) under Photoirradiation, Part-III† - Bhasin, C.P.; K.A. Parmar, Mrs.; Dave, R.S. (Asian Journal of Chemistry, 2010)
On irradiation with visible light six coordinated octahedral bipyridyl adduct of nickel(II) bis-(O,O-butylene dithiophosphate) is converted into five coordinated trigonal-bipyramidal complex. Four coordinated nickel(II) bis-(O,O-butylene dithiophosphate) on reaction with bipyridyl under photo-irradiation forms five coordinated complex again. In contrast to the above, four coordinated bis-(O,O-butylene dithiophosphate) nickel(II) on reaction with γ-picoline under photoirradiation forms six coordinated complex.